2021
DOI: 10.1002/jev2.12154
|View full text |Cite
|
Sign up to set email alerts
|

Roles of extracellular vesicles in the aging microenvironment and age‐related diseases

Abstract: Cellular senescence is a persistently hypoproliferative state with diverse stressors in a specific aging microenvironment. Senescent cells have a double-edged sword effect: they can be physiologically beneficial for tissue repair, organ growth, and body homeostasis, and they can be pathologically harmful in age-related diseases. Among the hallmarks of senescence, the SASP, especially SASP-related extracellular vesicle (EV) signalling, plays the leading role in aging transmission via paracrine and endocrine mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
94
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 305 publications
(304 reference statements)
1
94
1
Order By: Relevance
“…Maintaining the homeostasis of the regenerative microenvironment is essential for muscle growth and development. Based on the EVs delivery system, we constructed an endogenous beneficial microenvironment and activated the protection mechanism underpinning tissue regeneration, which is a promising method [ 61 , 62 ]. Increasing evidence has shown that EVs actively regulate angiogenesis in vascular endothelial cells by acting on blood vessel formation [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining the homeostasis of the regenerative microenvironment is essential for muscle growth and development. Based on the EVs delivery system, we constructed an endogenous beneficial microenvironment and activated the protection mechanism underpinning tissue regeneration, which is a promising method [ 61 , 62 ]. Increasing evidence has shown that EVs actively regulate angiogenesis in vascular endothelial cells by acting on blood vessel formation [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…As with AT, it has been reported that the number of ASCs obtainable from SAT decreases with age [101]; probably, the same happens for ASC-derived EVs [44]. Unfortunately, results on the differences in EV characteristics obtained from young and senescent cells are still conflicting [101]. Another important issue is the weight of the donors [102], as well as the presence of metabolic pathologies [29], which reasonably alter the quality and characteristics of the EVs obtained from those cells [109].…”
Section: Disadvantagesmentioning
confidence: 92%
“…In addition, a general limitation for all potential applications of EVs in therapy is the age of the tissue/cell donors. As with AT, it has been reported that the number of ASCs obtainable from SAT decreases with age [101]; probably, the same happens for ASC-derived EVs [44]. Unfortunately, results on the differences in EV characteristics obtained from young and senescent cells are still conflicting [101].…”
Section: Disadvantagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes were once considered to be the waste products of cells in the original research. Nowadays, more and more studies have shown that exosomes play important roles in organisms, such as cell-to-cell communication ( Ruhland et al, 2020 ; Schneider et al, 2021 ), immune response ( Kalluri and LeBleu, 2020 ; Su et al, 2020 ), cell growth and differentiation ( Yin et al, 2021 ; Zarnowski et al, 2021 ), as well as molecular transport ( Zhu Q. et al, 2021 ). Crucially, the concentration and phenotype of exosomes have been proved to reflect the state of their parental cells and associate with the occurrence and development of various diseases, such as cancers ( Jiang et al, 2021 ), infectious diseases ( Ning et al, 2021 ; Xie et al, 2021 ), metabolic, and cardiovascular diseases ( Kalluri and LeBleu, 2020 ).…”
Section: Introductionmentioning
confidence: 99%